Reliability and Fall Risk Detection for the BESTest and Mini-BESTest in Older Adults. Issue 2 (April 2019) - Anson, Eric; Thompson, Elizabeth; Ma, Lei; Jeka, John
Abstract : Background & Purpose: Test stability and test-retest reliability have not previously been reported for either the Balance Evaluation Systems Test (BESTest) or mini-BESTest (mBEST) in a population of older adults with nonspecific balance limitations. Furthermore, no criterion for identifying change greater than chance has been reported in older adults with nonspecific balance problems using either BESTest or mBEST scores. The purposes of this study were to determine test stability over time, test-retest reliability, to identify minimum detectable change for the BESTest and mBEST in a population of older adults with nonspecific balance problems. In addition, the ability of the BESTest and mBEST to identify past fallers was characterized. Methods: This was an observational study with 58 adults 65 years or older with a history of falls or self-reported balance problem. The BESTest and mBEST were administered to all participants at the beginning and end of 4 weeks. Test-retest reliability was calculated with intraclass correlations, and minimum detectable change was calculated at the 95% confidence level (MDC95 ). Receiver operating characteristics were used to characterize the sensitivity and specificity of the BESTest and mBEST to identify older adults who had previously fallen. Results: Balance scores did not significantly change over a 4-week period. Test-retest reliability for the BESTest (0.86) and mBEST (0.84) was good to excellent. MDC95 scores were identified for the BESTest (8.9) and mBEST (4). Conclusions: The BESTest and mBEST scores were stable and reliable over a period of 4 weeks for a population of older adults with self-reported balance problems or a history of falling. MDC95 scores allow interpretation of change in BESTest and mBEST scores following rehabilitation.